Rigid amphipathic nucleosides suppress reproduction of the tick-borne encephalitis virus12. Issue 3 (8th January 2016) - Orlov, Alexey A.; Chistov, Alexey A.; Kozlovskaya, Liubov I.; Ustinov, Alexey V.; Korshun, Vladimir A.; Karganova, Galina G.; Osolodkin, Dmitry I.
Abstract : Rigid amphipathic fusion inhibitors (RAFIs), 5-arylethynyl uracil nucleosides with bulky aryl groups, appeared to have considerable activity against tick-borne encephalitis virus (TBEV) in cell culture. Abstract : Rigid amphipathic fusion inhibitors (RAFIs), 5-arylethynyl uracil nucleosides with bulky aryl groups, appeared to have considerable activity against tick-borne encephalitis virus (TBEV) in cell culture. The rigid ethynyl linker and perylene residue are essential structural prerequisites for high activity, giving EC50 values of 18 and 24 nM for 5-(perylen-3-yl)ethynyl- arabino -uridine and 5-(perylen-3-yl)ethynyl-2′- deoxy -uridine, respectively, upon simultaneous mixing of the compounds, cells and virus.